A RARE CASE OF HIGHEST LITTER SIZE WITH COMPLICATED PREGNANCY IN A CROSSBRED GILT - KARTHICKEYAN, S M K; GOPINATHAN, A; RAMESH, J; SIVASELVAM, S N (The Indian Journal of Animal Reproduction, 2023)
Highest litter size of 22 numbers in a 75 per cent crossbred (Large White Yorkshire X Desi) gilt was obseNed;however, dam and all the piglets died due to pre-partum complications. The reasons and the earlier records ofsuch high litter size have been discussed.
Keywords: High litter size; Complicated pregnancy; Crossbred pigs; India